Influence of antimicrobial solutions in the decontamination and adhesion of glass-fiber posts to root canals - Gisele Aihara HARAGUSHIKU; Eduardo Donato Eing Engelke BACK; Paulo Henrique TOMAZINHO; Flares BARATTO FILHO; Adilson Yoshio FURUSE (University of São Paulo, 2015)
AbstractObjective This study evaluated the effect of root canal disinfectants on the elimination of bacteria from the root canals, as well as their effect on glass-fiber posts bond strength.Material and Methods Fifty-three endodontically treated root canals had post spaces of 11 mm in length prepared and contaminated with E. faecalis. For CFU/ml analysis, eight teeth were contaminated for 1 h or 30 days (n=4). Teeth were decontaminated with 5% NaOCl, 2% CHX, or distilled water. As control, no decontamination was conducted. After decontamination, sterile paper points were used to collect samples, and CFU/ml were counted. For push-out, three groups were evaluated (n=15): irrigation with 2.5% NaOCl, 2% CHX, or sterile distilled water. A bonding agent was applied to root canal dentin, and a glass-fiber post was cemented with a dual-cured cement. After 24 h, 1-mm-thick slices of the middle portion of root canals were obtained and submitted to the push-out evaluation. Three specimens of each group were evaluated in scanning electron microscopy (SEM). Data were analyzed with one-way ANOVA and Dunnett's T3 test (α=0.05).Results The number of CFU/ml increased from 1 h to 30 days of contamination in control and sterile distilled water groups. Decontamination with NaOCl was effective only when teeth were contaminated for 1 h. CHX was effective at both contamination times. NaOCl did not influence the bond strength (p>0.05). Higher values were observed with CHX (p<0.05). SEM showed formation of resin tags in all groups.Conclusion CHX showed better results for the irrigation of contaminated root canals both in reducing the bacterial contamination and in improving the glass-fiber post bonding.